Prophylactic use of antibiotics as per SIGN 104 guidelines versus routine antibiotic prophylaxis for prevention of surgical site infection in clean and clean contaminated ENT surgical procedures: a comparative study - Bharath, M.; Galagali, J. R.; Mishra, Awadhesh Kumar; Mallick, Ajay; Nikhilesh, E. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Many clinicians continue to use antibiotic prophylaxis routinely in all surgical procedures, ignoring the guidelines issued by policy makers. In this prospective study we compared the rate of surgical site infection (SSI) in patients who received prophylactic antibiotics as a routine; with the rate of SSI in patients getting antibiotics strictly as per SIGN 104 Guidelines, for clean and clean contaminated procedures. Methods: The study population comprised 235 patients. Group A consisted of 119 patients having 77 (65%) males and 42 (35%) females while Group B had 116 patients - 71 (61%) males and 45 (39%) females. Group A received routine antibiotic prophylaxis in all cases, while Group B received antibiotic prophylaxis as per SIGN 104 guidelines only. Both the groups were followed up for one month post-operatively for SSI and complications. Results: SSI occurred in 2 patients (1.68%) in Group A and in 3 (2.59%) patients in Group B. There was no significant difference in the rate of SSI between the two groups (p=0.68). Procedure wise maximum SSI occurred in tympanoplasty and laryngectomy. Due to infection one case of tympanoplasty had graft failure and one case of laryngectomy had delayed wound healing. No major complications related to infection or antibiotic use occurred in either group. Conclusions: Selective use of antibiotic prophylaxis as per SIGN 104 Guidelines does not lead to increase in SSI in clean and clean contaminated ENT procedures.